A Review of Numerical Studies of Wave Impacts on Marine Structures - ZHANG Nianfan, XIAO Longfei, CHEN Gang (Shanghai Jiaotong Daxue xuebao, 2024)
Wave impact is a strongly nonlinear interaction between waves and structures, and its load usually has the characteristics of a large peak value and short duration. In recent years, the extreme environment has frequently led to severe wave impacts on marine structures, resulting in loss of life and property, thus making the issue of wave impact become a great concern. For the complicated impact process, the theoretical analysis and model experiments can only provide simplified analytical solution and limited information on the slamming flow field. Therefore, numerical simulation has gradually become an effective means to study the issue of wave impact. Scholars at home and abroad have conducted a large number of numerical investigations on the load characteristics of wave impact, impact process, and its influencing factors on marine structures, gaining numerous important research conclusions. In this paper, the current progress, existing methods, and important conclusions of the numerical study of wave impact on marine structures are reviewed, which can provide useful references for further research on the numerical simulation of wave impact.